Modulation of Trehalose Dimycolate and Immune System by Rv0774c Protein Enhanced the Intracellular Survival of Mycobacterium smegmatis in Human Macrophages Cell Line - Kumar, Arbind; Saini, Varinder; Kumar, Anjani; Kaur, Jasbinder; Kaur, Jagdeep (Frontiers in Cellular and Infection Microbiology, 2017)
Mycobacterium tuberculosis Rv0774c protein was reported previously to express under stress conditions. Therefore, Rv0774c gene was cloned and expressed in Mycobacterium smegmatis, a surrogate host, to determine its role in bacterial persistence and immune modulation in natural environment. The bacterial colonies expressing Rv0774c (Ms_rv0774c) were larger, smoother, more moist, and flatter than the control ones (Ms_ve). Enhanced survival of Ms_rv0774c after treatment with streptomycin was observed when compared with control. The cell envelope of Ms_rv0774c was demonstrated to have more trehalose di-mycolate (TDM) and lesser amount of mycolylmannosylphosphorylheptaprenol (Myc-PL) in comparison to control. Higher intracellular survival rate was observed for Ms_rv0774c as compared to Ms_ve in the THP-1 cells. This could be correlated to the reduction in the levels of reactive NO and iNOS expression. Infection of macrophages with Ms_rv0774c resulted in significantly increased expression of TLR2 receptor and IL-10 cytokines. However, it lowered the production of pro-inflammatory cytokines such as IL-12, TNF-α, IFN-γ, and MCP-1 in Ms_rv0774c infected macrophages in comparison to the control and could be associated with decreased phosphorylation of p38 MAPK. Though predicted with high antigenicity index bioinformatically, extracellular in nature and accessible to host milieu, Rv0774c was not able to generate humoral response in patient samples. Overall, the present findings indicated that Rv0774c altered the morphology and streptomycin sensitivity by altering the lipid composition of M. smegmatis as well as modulated the immune response in favor of bacterial persistence.